Análisis de cartera vencida del rubro de agua potable en el GAD Municipal del cantón Chillanes oficina de San Jose del Tambo durante los periodos 2019 -2020 - Freire Chaquinga, Diego Alexi (2021)
The GAD is an administrative and governmental institution whose objective is to provide all residents with the services and rights that they have within the area where it operates, always with equality, transparency, honesty and leadership, it is also in charge of make administrative decisions which are mainly destined to works such as infrastructure, basic services such as drinking water, electricity, etc. Although we have said that the services are necessary, it is also necessary to pay for them, since, thanks to this, the system of said service can be improved or maintained, so that its users can continue to enjoy these benefits, but it is here where users also do not pay, causing the service to remain stagnant, which delays one of the objectives of the GAD, which is to ensure sustainable development within the country. This is where the research seeks to recommend the procedures that other service companies carry out when it comes time to deal with delinquent clients, so that different retaliations are taken based on the amount of overdue balance that users carry over time.